Tingkatkan Penggunaan Model Quantum Teaching Dan Snowball Throwing Dalam Pembelajaran Ips Dapat Meningkatkan Belajar Siswa Kelas Iii Sd Negeri No.39 Pasar Gompong Kec.Lengayang Semester I Tahun Pelajaran 2016/2017 - Nurlaili Nurlaili (Fakultas Sastra Universitas Ekasakti, 2017)
Activities and student learning outcomes Class III Elementary School No. 39 Market Gompong , District Lengayang district, South Coastal , in the school year 201 6 /201 7 in learning about social studies teaching material Know the use of money according to need, less reach expectations, which are caused by the use of the learning model is less varied. To resolve the issue used collaborative learning model Quantum Teaching and Snowball Throwing . To test the effectiveness of the learning model in order to improve the activity and student learning outcomes, the procedures of classroom action research, which was conducted over two cycles.Each cycle taking the following four steps: (1) planning, (2) implementation, (3) observation, and (4) reflection. Through a variety of instruments and techniques of data collection, the result of research. To then be discussed by the techniques that have been set. Finally obtained a conclusion in order to address the subject matter of the study. The conclusions were as follows: (1) measures the use of collaborative models of Quantum Teaching and Snowball Throwing to increase the activity and student learning outcomes Class III Elementary School No. 39 Market Gompong in learning about social studies teaching material to know the use of money as needed, including: (1) plan in accordance with the regulations, (2) carry out teaching in accordance with the plan,(3) evaluate the student's ability to meet any demands of learning, and (4) follow up on the results carefully. (2) Increased activity and student learning outcomes in social studies learning about teaching materials Getting to know the use of money in accordance with the requirements after use collaborative use of models Quantum Teaching and Snowball Throwing, occurs gradually. Improved student learning activities gradually are shown in several ways, such as participation, interest, and ability to make presentations. So even with improved learning outcomes, gradually able to shown students to meet any demands of learning. (3) The use of collaborative models of Quantum Teaching and Snowball Throwing in learning about social studies teaching material to know the use of money in accordance with the requirements shown to increase the activity and student learning outcomes Class III Elementary School No. 39 Market Gompong .